Криогенные газовые машины - Суслов А. Д. Александр Дмитриевич; Гороховский Г. А. Герман Алексеевич; Полтараус В. Б. Василий Борисович; Горшков А. М. Александр Михайлович (Москва, Машиностроение, 1982)
Авт. указаны на обороте тит. л.